Report of the Activities Completed During Sabbatical Leave in the Fall of 2007. - Schmitt, Elena (Distribution: Fall 2007 ; World Languages and Literatures., 2007)
Research completed during this leave focused on the already collected data for an article outlining distinctions between language attrition and incomplete acquisition, and on a new project and new data for research on how literacy or its lack in a minority language affects the degree of language maintenance and development.
Keywords: dept.wll; faculty_collection; sabbatical_report

Book Review: bilingualism: the sociopragmatic-psycholinguistic interface - Schmitt, Elena (Language, 2007)
Keywords: book.review; dept.wll

Research on language education through programmes of study and residence abroad: recent publications - Verplaetse, Lorrie Stoops (International Journal of Bilingual Education and Bilingualism, 2007)
Keywords: dept.wll